NUMERICAL MODELING OF SUPERHEATED STEAM CONDENSATION IN HEAT EXCHANGER - AMIR SOFFIAN, MUHAMMAD ASHRAF (IRC, 2021)
The Granulator Atomization Air heater is a type of tube and shell heat exchanger, which experiences thinning at the tube inlets of superheated steam.